Evaluation and usability testing on integrated forest and land fire patrol application in Sumatera Region. Issue 1 (1st December 2022) - Gusmendasari, R; Sitanggang, L S; Ardiansyah, F; Syaufina, L; Rahmawan, H; Trisminingsih, R; Wulandari
Abstract: One of the causes of the annual decline in the forest area in Indonesia is forest and land fires. To prevent forest and land fires, the government carries out integrated patrol activities by forming a team for fire-prone area. A mobile application called Patroli Karhutla has been developed to facilitate the data recording obtained by the integrated patrol team. This study aims to produce recommendations for improvement in terms of usability based on evaluation and testing by users of the application in Sumatra. Evaluation and improvement of the application were conducted before testing. Testing includes two components, namely task success and efficiency, using several methods such as observation, interviews, focus group discussions, and concurrent think aloud. The test results on task success based on the level of success showed that the average task success of Patroli Karhutla application reached the target except for the profile and observation report. The average task success in scenarios done by respondents is 83.9 based on the indicators. The geometric mean-time of work on the scenario of the respondents has not reached the target and got two times the specified benchmark time. Errors and comments provided during testing by respondents produce some recommendations for improvement in the application for further development.